THE ROLE OF PEOPLE’S BUSINESS CREDIT (KUR) IN THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs), (CASE STUDY ON CURRENT DRINKING MSMES IN THE SOUTH JAKARTA REGION) - Khafifah, Aura; Sebayang, Karuniana Dianta; Mukhtar, Saparuddin (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the economy of a country or a region, Indonesia is no exception. Business in the beverage sector does not always complement the food business. The place or location of this research is the contemporary beverage MSMEs in the South Jakarta area. The research was carried out for two months starting from February 2022 to March 2022 which was carried out in stages. In compiling the report, it was concluded that the financing of KUR funds from BRI for the contemporary beverage MSMEs in the South Jakarta area was indeed very effective. The current drink sellers admitted that after getting KUR funds from BRI, their business grew, starting from the turnover they got to the required infrastructure. This is because the financing of KUR funds from BRI does not only provide assistance in the form of funds but also monitors the development of each of these MSME businesses, so that MSME entrepreneurs feel very helped. The role of KUR financing in the development of contemporary beverage MSMEs in the South Jakarta area with this financing can increase business productivity, especially for MSME businesses in Tebet, South Jakarta. This shows that KUR funds provided by BRI can have a positive effect on the development of MSMEs, this can be seen from the initial profits and profits after receiving KUR funds always increase so that MSME entrepreneurs feel very helped. The role of KUR financing in the development of contemporary beverage MSMEs in the South Jakarta area with this financing can increase business productivity, especially for MSME businesses in Tebet, South Jakarta. This shows that KUR funds provided by BRI can have a positive effect on the development of MSMEs, this can be seen from the initial profits and profits after receiving KUR funds always increase so that MSME entrepreneurs feel very helped. The role of KUR financing in the development of contemporary beverage MSMEs in the South Jakarta area with this financing can increase business